Students Perception on Soft Skills in Faculty of Medicine, Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Sulistiyana, Catur Setiya; Fauzan, Zamzam Ahmad; Permatasari, Tissa Octavira; Khasanah, Uswatun (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Soft skills is important attributes of professionalism in the practice of medicine. Soft skills to be known as person's ability beyond knowledge, intelligence, or competence. Faculty of Medicine in Universitas Swadaya Gunung Jati, Cirebon, Indonesia, has used various learning methods to support students' skills, allowing students to have different perspectives in understanding soft skills. Aims: To identify the perception of medical students at Faculty of Medicine, Swadaya Gunung Jati University, in the pre-clinical stage towards soft skills. Methods: This was an observational descriptive study. Respondents were selected using Stratified Random Sampling techniques, sample size was 262 respondents were obtained from semester 2, 4, 6 and 8. This study used primary data with 42 statement items with univariate analysis. Results: From 262 respondents, of 93.1% students (244) have a good perception of the definition of soft skills. As many as 50.4% (123) of 262 respondents have a good perception of time management. As many as 81.3% (213) of 262 respondents have a good perception of critical thinking. 73.7% (193) of 262 respondents have a good perception of teamwork. As many as 87.4% (229) of 262 respondents have a good perception of public speaking. Conclusion: This study showed medical student perception of soft skills regarding definition, time management skills, critical thinking, teamwork, and public speaking had a good perception. In the future, Faculty needs to provide space for students to develop these soft skills through training or interprofessional education and other programs. Received: 10 September 2024 | Reviewed: 16 October 2024 | Revised: 23 October 2024 | Accepted: 31 October 2024.